2001
DOI: 10.1152/ajplung.2001.281.1.l231
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein interactions with neutral and acidic phospholipid films

Abstract: The captive bubble tensiometer was employed to study interactions of phospholipid (PL) mixtures of dipalmitoylphosphatidylcholine (DPPC) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) or 1-palmitoyl-2-oleoyl-sn-glycero-3-[phospho-rac-(1-glycerol)] (POPG) at 50 microg/ml with physiological levels of the surfactant protein (SP) A SP-B, and SP-C alone and in combination at 37 degrees C. All surfactant proteins enhanced lipid adsorption to equilibrium surface tension (gamma), with SP-C being most effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 43 publications
4
61
0
Order By: Relevance
“…Compressibility at ␥ 20 (C 20 ) was 0.078 Ϯ 0.020. As reported previously, control BLES adsorbed at 50 g/ml required ϳ60% surface area reduction to lower ␥ from equilibrium (23 mN/m) to near zero during the first compression (16,35,42).…”
Section: Fig 4 Typical Negative Electrospray Ion Mass Spectra For Asupporting
confidence: 79%
See 1 more Smart Citation
“…Compressibility at ␥ 20 (C 20 ) was 0.078 Ϯ 0.020. As reported previously, control BLES adsorbed at 50 g/ml required ϳ60% surface area reduction to lower ␥ from equilibrium (23 mN/m) to near zero during the first compression (16,35,42).…”
Section: Fig 4 Typical Negative Electrospray Ion Mass Spectra For Asupporting
confidence: 79%
“…Effect of Free Radical Exposure on Surfactant Function-The effects of free radical exposure on surfactant function were studied with the CBT (16,35). With this apparatus, the ability of a surfactant to adsorb to the interface is assessed, after which surface area compression-expansion isotherms are performed, either quasi-statically or dynamically, to evaluate the surface properties of the sample under conditions that mimic…”
Section: Effect Of Free Radical Exposure On Surfactantmentioning
confidence: 99%
“…To resist or reverse the inactivation, the phospholipid components of lung surfactant must overcome these barriers by adsorbing more rapidly than albumin and/or effectively replacing the albumin molecules at the interface. Chitosan may outperform the nonionic polymers in mitigating the electrostatic barrier imposed by albumin by providing extra positive charges, similar to the function of lung surfactant proteins (21,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting DPPC enrichment is considered necessary in order for the monolayer to achieve the low surface tensions required to stabilize the lung. Recently, a number of physicochemical studies have demonstrated that low surface tension can be achieved with smaller surface area reductions than would be predicted by the squeeze-out mechanism (43)(44)(45)(46). It has consequently been proposed that sorting or refining of surfactant lipids occurs during adsorption so as to generate a monolayer already enriched in DPPC (3-7, 37, 38).…”
Section: Discussionmentioning
confidence: 99%
“…Recent physicochemical measurements have demonstrated that surface area reductions required to attain surface tensions near 0 mN/m during initial film compression of adsorbed surfactant films can be lower than that predicted by the DPPC content of surfactant (37,(43)(44)(45)(46). These observations led to the proposal that the surface monolayer may become enriched in DPPC during adsorption (3-6, 37, 38).…”
mentioning
confidence: 99%